Robotic process automation (RPA) and agents with BPMS to increase autonomous capability and operational improvement in organizations: a practical assessment - Jorcín, Renato; Delgado, Andrea; Calegari, Daniel (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
Robotic Process Automation (RPA) tools have recently incorporated autonomous LLM-based agents to automate complex human-interaction tasks without disrupting internal systems. Its use within Business Process Management Systems (BPMS) enables process optimization, error minimization, and reduced time commitment. This study presents a practical evaluation of UiPath, Microsoft Power Automate, and Automation Anywhere, and their integration with Camunda BPMS through three automation scenarios. The results indicate that all tools contribute to increasing autonomous capacity and improving operational processes, with strengths in different characteristics.